2023
DOI: 10.1007/s11908-023-00816-6
|View full text |Cite
|
Sign up to set email alerts
|

What is New in Augmented Renal Clearance in Septic Patients?

Laura Baptista,
Inês Moura,
Catarina Mendes Silva
et al.

Abstract: Purpose of Review In this narrative review encompassing relevant scientific publications regarding critically ill patients in the last 5 years, we discuss key questions regarding the concept, pathophysiology, identification, epidemiology, and implications of augmented renal clearance (ARC) in the treatment of sepsis. Recent Findings Mathematical estimates of renal function show low accuracy when evaluating renal function in the intensive care unit, jeopard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Moreover, in critically ill patients with ARC, both the CG formula and MDRD formula tend to underestimate GFR when compared to 8-h or 24-h creatinine clearance [ 3 ]. Baptista elucidated in the most recent review that, for critically ill patients, the estimated GFR derived from formulas exhibits a tenuous correlation with measured GFR, emphasizing the superior accuracy of utilizing measured GFR within the ICU context [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in critically ill patients with ARC, both the CG formula and MDRD formula tend to underestimate GFR when compared to 8-h or 24-h creatinine clearance [ 3 ]. Baptista elucidated in the most recent review that, for critically ill patients, the estimated GFR derived from formulas exhibits a tenuous correlation with measured GFR, emphasizing the superior accuracy of utilizing measured GFR within the ICU context [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ARC is notably high, predominantly manifesting in patients experiencing trauma, severe infection, or major surgery, consistent with findings from prior investigations. Earlier research has demonstrated ARC incidence rates ranging from 22.1 % to 65.1 %, with identified risk factors encompassing age, male gender, trauma, severe infection, and vasopressor usage [ 29 ]. Notably, in Udy's study, GFR was estimated using 8-h creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%